2018
DOI: 10.26477/jbcd.v30i4.2553
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Breastfeeding Duration on the Development of Normal Occlusal Features of the Primary Dentition among Baghdad Preschool Children

Abstract: Background: Normal occlusal features of primary dentition are crucial for normal development of the permanent dentition. Breastfeeding is an important factor for both general and dental health of children. Aim: The aim of the present study is to assess the impact of the breastfeeding duration on the prevalence of normal occlusal features of the primary dentition among preschool children in Baghdad. Materials and Methods: The sample was 630 Iraqi children (270- boys, 360 girls), aged 3-5 years selected from fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…However, Holman and Yamaguchi (16) and Aziz (18) reported contradicting results in Kerbala. Viggiano et al (21) found that breastfeeding is the ideal Although breastfeeding is imperative for the good development of the entire craniofacial complex (5) , the eruption process depends on many other factors, such as breast milk composition, which was found to be positively related to maternal BMI and adiposity (22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Holman and Yamaguchi (16) and Aziz (18) reported contradicting results in Kerbala. Viggiano et al (21) found that breastfeeding is the ideal Although breastfeeding is imperative for the good development of the entire craniofacial complex (5) , the eruption process depends on many other factors, such as breast milk composition, which was found to be positively related to maternal BMI and adiposity (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Nursing is the best orthopedic intervention to achieve a mature individual's harmonic growth, which is essential for the proper growth of the complete craniofacial complex throughout the most critical period of an infant's life (5) . The primary tooth begins to erupt into the oral cavity after the sixth month of life through a complex and highly controlled process (6) .…”
Section: Introductionmentioning
confidence: 99%
“…The normal occlusion of deciduous teeth is characterized by the following clinical features [30][31][32][33][34][35][36][37]:…”
Section: Introductionmentioning
confidence: 99%
“…-Overbite, which is the vertical overlap or the amount of space in millimeters that the upper central incisor covers the lower central incisor. A normal overbite is generally considered to be in the range of 2-3 mm [30][31][32][33][34][35][36]. -Overjet, which is the space in millimeters between the buccal face of the lower central incisor and the palatal face of the upper central incisor.…”
Section: Introductionmentioning
confidence: 99%